A double-layer lithium ion sieve fiber material and its preparation method and application

By using a double-layer lithium ion sieve fiber material and using flexible and rigid support to combine manganese ions and titanium ion sieve, the problems of degradation in the adsorption performance and serious dissolution loss in the process of lithium extraction in the salt lake are solved, and efficient lithium ion adsorption and good material circulation performance are achieved.

CN118159422BActive Publication Date: 2025-03-07GUANGDONG BRUNP RECYCLING TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380012565.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2025-03-07
Estimated Expiration
2043-12-21

AI Technical Summary

Technical Problem

The existing ion sieves have problems such as degraded adsorption performance, severe dissolution loss and poor circulation performance during the lithium extraction process of salt lakes.

Method used

The double-layer lithium ion sieve fiber material is used, the core layer is composed of a flexible support and a manganese ion sieve, and the cladding layer is composed of a rigid support and a titanium ion sieve. It is prepared by spinning process and acid leaching pore technology to optimize the porosity and specific surface area of ​​the material.

Benefits of technology

It improves the adsorption performance of lithium ions and the cyclic performance of the material, reduces the dissolution of manganese ion sieve, and enhances the water pressure resistance and structural integrity of the fiber material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004633977810000121
    Figure BDA0004633977810000121
  • Figure BDA0004633977810000122
    Figure BDA0004633977810000122
  • Figure BDA0004633977810000131
    Figure BDA0004633977810000131
Patent Text Reader

Abstract

The present disclosure discloses a double-layer lithium ion sieve fiber material and its preparation method and application, which relate to the field of lithium resource technology. The double-layer lithium ion sieve fiber material includes a core layer and a coating layer, the core layer includes a flexible carrier and a manganese ion sieve dispersed in the flexible carrier, the components of the flexible carrier include soft polyvinyl chloride and hydrophilic polyethersulfone, and a plurality of first holes are constructed on the flexible carrier; the coating layer includes a rigid carrier and a titanium ion sieve dispersed in the rigid carrier, the components of the rigid carrier include poly(p-phenylene terephthalamide) and poly(hexamethylene adipamide), and a plurality of second holes are constructed on the flexible carrier. The double-layer lithium ion sieve fiber material provided by the present disclosure is rigid on the outside and soft on the inside, and has good water pressure resistance and fracture resistance. At the same time, the manganese ion sieve has less dissolution loss, and has excellent cycle performance and lithium ion adsorption performance, and can be widely used in lithium extraction from brine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of lithium resource technology, and in particular to a double-layer lithium ion sieve fiber material and a preparation method and application thereof. Background Art

[0002] In the field of lithium extraction technology from salt lakes, the adsorption method has good selectivity, and lithium ion adsorption can also be achieved for brine with a high magnesium-lithium ratio. Ion sieve is an important adsorbent commonly used for lithium extraction from salt lakes, but ion sieve is generally a powder raw material, which has the problems of poor fluidity and difficult recycling. In this regard, it is generally solved by granulation or film casting. The ion sieve after granulation is used to fill the column, which is easier to recycle. However, the adsorption performance of the ion sieve after granulation and film casting is generally lower than that of the powder ion sieve.

[0003] At present, innovative research on extracting lithium from salt lakes using adsorption methods is emerging in an endless stream. It is of great significance to develop an adsorption material with strong adsorption capacity, small ion sieve dissolution loss and good cycle performance.

[0004] In view of this, the present disclosure is proposed. Summary of the invention

[0005] The purpose of the present disclosure is to provide a double-layer lithium ion sieve fiber material and a preparation method and application thereof.

[0006] The present disclosure is implemented as follows:

[0007] In a first aspect, the present disclosure provides a double-layer lithium ion sieve fiber material, which includes a core layer and a coating layer from inside to outside;

[0008] The core layer includes a flexible carrier and a manganese ion sieve dispersed in the flexible carrier, the flexible carrier is composed of soft polyvinyl chloride and hydrophilic polyethersulfone, and a plurality of first holes are constructed on the flexible carrier;

[0009] The coating layer comprises a rigid carrier and a titanium ion sieve dispersed in the rigid carrier, the rigid carrier is composed of poly(p-phenylene terephthalamide) and poly(hexamethylene adipamide), and a plurality of second holes are constructed on the flexible carrier.

[0010] In an optional embodiment, the thickness ratio of the core layer to the cladding layer is 1:(1-3).

[0011] In an optional embodiment, the specific surface area of ​​the core layer is 5m 2 / g-12m 2 / g.

[0012] In an optional embodiment, the specific surface area of ​​the coating layer is 5m 2 / g-12m 2 / g.

[0013] In an optional embodiment, the mass ratio of the manganese ion sieve, the soft polyvinyl chloride and the hydrophilic polyether sulfone is (25-40): (70-100): (25-50).

[0014] In an optional embodiment, the mass ratio of the titanium ion sieve, the poly(p-phenylene terephthalamide) and the poly(hexamethylene adipamide) is (25-40):(45-80):(25-50).

[0015] In an optional embodiment, the density of the soft polyvinyl chloride is 1.2 g / cm 3 -1.3g / cm 3 , the yield strength is 15MPa~25MPa.

[0016] In an optional embodiment, the double-layer lithium ion sieve fiber material is a fiber membrane or a fiber wire.

[0017] In an optional embodiment, the diameter of the fiber line is 0.5 μm-100 μm.

[0018] In a second aspect, the present disclosure provides a method for preparing a double-layer lithium ion sieve fiber material, comprising:

[0019] The manganese ion sieve, soft polyvinyl chloride, hydrophilic polyethersulfone, core layer solvent and sodium bicarbonate are mixed to form a core layer spinning solution;

[0020] The titanium ion sieve, poly(p-phenylene terephthalamide), poly(hexamethylene adipamide), a coating layer solvent and sodium carbonate are mixed to form a coating layer spinning solution;

[0021] Spinning the core layer spinning solution and the cladding layer spinning solution to form a double-layer fiber intermediate product in which the cladding layer covers the core layer;

[0022] The double-layer fiber intermediate product is subjected to acid leaching to form pores, and then dried to obtain the double-layer lithium ion sieve fiber material.

[0023] In an optional embodiment, the mass ratio of the manganese ion sieve, the soft polyvinyl chloride, the hydrophilic polyethersulfone, the core layer solvent and the sodium bicarbonate is (25-40): (70-100): (25-50): (135-235): (15-30).

[0024] In an optional embodiment, the core layer solvent includes at least one of dimethylformamide and N-methylpyrrolidone.

[0025] In an optional embodiment, the core layer solvent includes dimethylformamide and N-methylpyrrolidone in a mass ratio of (75-135):(60-100).

[0026] In an optional embodiment, the mass ratio of the titanium ion sieve, the poly(p-phenylene terephthalamide), the poly(hexamethylene adipamide), the coating layer solvent and the sodium carbonate is (25-40):(45-80):(25-50):(140-250):(15-30).

[0027] In an optional embodiment, the coating layer solvent includes at least one of methanesulfonic acid and m-cresol.

[0028] In an optional embodiment, the coating layer solvent comprises methanesulfonic acid and m-cresol in a mass ratio of (90-150):(50-100).

[0029] In an optional embodiment, the spinning includes dry spinning, wet spinning or electrospinning.

[0030] In an optional embodiment, the spinning is coaxial electrospinning.

[0031] In an optional embodiment, the spinning environment temperature of the coaxial electrospinning is 15° C.-25° C., the ambient humidity is less than 30%, and the spinning voltage is 15 kv-25 kv.

[0032] In an optional embodiment, during the coaxial electrospinning, the propulsion flow rate of the core layer spinning solution is 0.18 mL / h-0.25 mL / h, and the propulsion flow rate of the coating layer spinning solution is 0.10 mL / h-0.15 mL / h.

[0033] In an optional embodiment, the acid used for pickling is hydrochloric acid.

[0034] In an optional embodiment, the acid leaching time is 0.5h-1.5h.

[0035] In an optional embodiment, the method for preparing the core layer spinning solution includes: mixing the core layer solvent with the soft polyvinyl chloride and the hydrophilic polyether sulfone, heating to 70°C-85°C, stirring for 5h-7h, cooling to room temperature, and then adding the sodium bicarbonate, stirring evenly, and then adding the manganese ion sieve, stirring evenly to obtain the core layer spinning solution.

[0036] In an optional embodiment, the coating layer solvent includes methanesulfonic acid and isocresol, and the method for preparing the coating layer spinning solution includes: first mixing the methanesulfonic acid and the poly(p-phenylene terephthalamide), heating to 70°C-85°C, and stirring for 5h-6h to obtain a poly(p-phenylene terephthalamide) solution; then mixing the isocresol with the poly(hexamethylene adipamide), heating to 70°C-85°C, and stirring for 5h-6h to obtain a poly(hexamethylene adipamide) solution; mixing the poly(p-phenylene terephthalamide) solution and the poly(hexamethylene adipamide) solution, stirring evenly, cooling to room temperature, and then adding the sodium carbonate, stirring evenly, and then adding the titanium ion sieve, stirring evenly to obtain the coating layer spinning solution.

[0037] In a third aspect, the present disclosure provides the use of a double-layer lithium ion sieve fiber material as described in any of the aforementioned embodiments or a double-layer lithium ion sieve fiber material prepared by the preparation method of the double-layer lithium ion sieve fiber material as described in any of the aforementioned embodiments as an adsorbent in lithium extraction from salt lake brine.

[0038] In an optional embodiment, the salt lake brine includes at least one of original brine and old brine.

[0039] The present disclosure has the following beneficial effects:

[0040] The double-layer lithium ion sieve fiber material provided by the present disclosure optimizes the formula of the core layer material and the coating layer material, and obtains a fiber material that is rigid on the outside and soft on the inside. The coating layer fiber has good rigidity, high strength, and is not easy to break, which plays a good supporting role, can well resist water pressure, and better maintain the structural integrity of the fiber material; the core layer fiber has good flexibility, which can further reduce the probability of material breakage during use. The core layer material does not directly contact the brine during use, and the present disclosure improves the inward penetration and infiltration of brine by using hydrophilic polyethersulfone to modify the core layer material, thereby improving the adsorption performance of lithium ions. The double-layer lithium ion sieve fiber material provided by the present disclosure places the manganese ion sieve that is more easily dissolved in the core layer of the fiber material, and the coating layer fiber material forms a protective layer for the manganese ion sieve, reducing the direct contact between the acid and the manganese ion sieve, inhibiting the corrosion of the acid to the manganese ion sieve, thereby reducing the dissolution of the manganese ion sieve and ensuring the circulation performance of the fiber material.

[0041] The preparation method of the double-layer lithium ion sieve fiber material provided in the present invention is prepared by a spinning process technology. The fiber material obtained by spinning has a high porosity and a large specific surface area. Then, pores are formed by an acid leaching pore-forming process. Since the present invention adopts sodium carbonate as a coating layer fiber pore-forming agent and sodium bicarbonate as a core layer fiber pore-forming agent, the fiber can form more pores. At the same time, the bubbles generated when the core layer fiber is pore-formed are discharged from the inside to the outside, further promoting the formation of pores. During the acid leaching process, the precipitation of carbon dioxide further increases the porosity of the fiber material, so that the lithium ion sieve exposes more adsorption sites and increases the adsorption amount of lithium ions. The prepared double-layer lithium ion sieve fiber material can be widely used in brine for lithium extraction. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present disclosure clearer, the technical scheme in the embodiments of the present disclosure will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0043] The present disclosure provides a double-layer lithium ion sieve fiber material, which includes a core layer and a coating layer, and the thickness ratio of the core layer to the coating layer is 1: (1-3).

[0044] The core layer includes a flexible carrier and a manganese ion sieve dispersed in the flexible carrier. The flexible carrier is composed of soft polyvinyl chloride and hydrophilic polyethersulfone. A plurality of first holes are constructed on the flexible carrier. The specific surface area of ​​the core layer is 5m 2 / g-12m 2 / g coating layer includes a rigid carrier and a titanium ion sieve dispersed in the rigid carrier. The rigid carrier is composed of poly(p-phenylene terephthalamide) and poly(hexamethylene adipamide). A plurality of second holes are constructed on the flexible carrier. The specific surface area of ​​the coating layer is 5m 2 / g-12m 2 / g.

[0045] Specifically, the raw materials of the core layer include the following components in parts by weight: 25-40 parts of manganese ion sieve, 70-100 parts of soft polyvinyl chloride, 25-50 parts of hydrophilic polyether sulfone, 135-235 parts of core layer solvent and 15-30 parts of sodium bicarbonate; the raw materials of the coating layer include the following components in parts by weight: 25-40 parts of titanium ion sieve, 45-80 parts of poly(p-phenylene terephthalamide), 25-50 parts of poly(hexamethylene adipamide), 140-250 parts of coating layer solvent and 15-30 parts of sodium carbonate.

[0046] Manganese ion sieves have a high affinity for lithium ions and good adsorption performance for lithium ions. However, during the adsorption and desorption of lithium ions, especially in the desorption stage, manganese dissolution is serious, which will cause certain water pollution during actual application. Titanium ion sieves have less dissolution, and titanium ion sieves are basically the ion sieves with the least water pollution.

[0047] In the present disclosure, the manganese ion sieve is arranged in the core layer and the titanium ion sieve is arranged in the coating layer. Since the dissolution loss rate of the titanium ion sieve is relatively small, it can fully contact with the brine to adsorb lithium ions, and the fiber strength of the coating layer is relatively large and not easy to break, and it can well resist water pressure and better maintain the structural integrity of the fiber material; the manganese ion sieve is placed in the core layer, and the fiber material of the coating layer can form protection for the manganese ion sieve of the core layer, reducing the direct contact of the manganese ion sieve with the acid during desorption, inhibiting the corrosion of the acid to the manganese ion sieve, and reducing the dissolution loss of the manganese ion sieve. At the same time, the hydrophilicity of the core layer material is relatively large, which can improve the inward permeability of the brine, improve the wettability of the core layer material, and increase the adsorption amount of lithium ions.

[0048] Among them, in the fiber material of the coating layer, the molecular chain of poly(p-phenylene terephthalamide) is rigid, has good strength, has high tensile strength and toughness; poly(hexamethylene adipamide) has high mechanical strength, large rigidity and high tensile strength. The present invention uses poly(p-phenylene terephthalamide) and poly(hexamethylene adipamide) as the skeleton material of the coating layer fiber, and the obtained coating layer material has high mechanical strength, plays a supporting role for the material, and can make the material have appropriate flexibility, the material is not easy to break, can resist water pressure well, better maintain the structural integrity of the fiber material, and improve the service life of the fiber material.

[0049] In the core fiber material, the density of soft polyvinyl chloride is 1.2g / cm 3 -1.3g / cm 3 The yield strength is 15MPa-25MPa. It has good softness and high elongation at break, which makes the material hard outside and soft inside, not easy to break and has good strength. At the same time, the core material is modified by adding hydrophilic polyethersulfone, which can improve the hydrophilicity of the core fiber material, improve the permeability and wettability of the core fiber material, and ensure the lithium ion adsorption effect of the core material.

[0050] Sodium carbonate is a pore-forming agent for the fiber material of the coating layer, and sodium bicarbonate is a pore-forming agent for the fiber material of the core layer. After the fiber material is spun, the fiber material is placed in an acid solution for immersion. Sodium carbonate and sodium bicarbonate will react chemically with the acid solution to produce carbon dioxide. The precipitation of carbon dioxide will cause the material to form many pores, thereby increasing the porosity of the fiber material. The core layer fiber material is coated with the fiber material of the coating layer. During acid immersion, the acid first contacts the fiber material of the coating layer and reacts with the sodium carbonate thereon to produce carbon dioxide. After the acid passes through the fiber material of the coating layer, it enters the fiber material of the core layer and reacts with the sodium bicarbonate on the fiber of the core layer to produce carbon dioxide. The reaction of sodium bicarbonate with acid is more intense than that of sodium carbonate with acid. The core layer fiber ensures that the core layer fiber material produces more bubbles through a more intense reaction. The bubbles produced in the core layer precipitate from the inside to the outside, further promoting the coating layer material to produce more pores. In the present disclosure, pores are formed by reacting sodium carbonate and sodium bicarbonate with acid, which can significantly increase the specific surface area of ​​the core layer and the coating layer, thereby having a more excellent adsorption effect.

[0051] Furthermore, the core layer comprises the following components in parts by weight: 28-38 parts of manganese ion sieve, 80-90 parts of soft polyvinyl chloride, 30-45 parts of hydrophilic polyether sulfone, 155-210 parts of core layer solvent and 20-28 parts of sodium bicarbonate; the coating layer comprises the following components in parts by weight: 28-38 parts of titanium ion sieve, 50-75 parts of poly(p-phenylene terephthalamide), 30-45 parts of poly(hexamethylene adipamide), 160-220 parts of coating layer solvent and 18-28 parts of sodium carbonate.

[0052] In certain embodiments, the weight of the manganese ion sieve can be, for example, 28 parts, 30 parts, 32 parts, 35 parts, 36 parts or 38 parts, or any range between two of them; the weight of the soft polyvinyl chloride can be, for example, 80 parts, 82 parts, 85 parts, 87 parts, 88 parts, 90 parts, or any range between two of them; the weight of the hydrophilic polyether sulfone can be, for example, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts or 45 parts, or any range between two of them; the weight of the core layer solvent can be, for example, 155 parts, 165 parts, 175 parts, 185 parts, 195 parts, 200 parts, 205 parts or 210 parts, or any range between two of them; the weight of the sodium bicarbonate can be, for example, 20 parts, 22 parts, 25 parts, 26 The weight parts of the titanium ion sieve can be, for example, any one of 28 parts, 30 parts, 32 parts, 35 parts, 36 parts or 38 parts or any range between them; the weight parts of poly(p-phenylene terephthalamide) can be, for example, any one of 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts or any range between them; the weight parts of poly(hexamethylene adipamide) can be, for example, any one of 30 parts, 34 parts, 38 parts, 42 parts or 45 parts or any range between them; the weight parts of the coating layer solvent can be, for example, any one of 160 parts-220 parts or any range between them; the weight parts of sodium carbonate can be, for example, any one of 18 parts-28 parts or any range between them.

[0053] In the present disclosure, the core layer solvent can be used as long as it can dissolve the components of the core layer. Similarly, the coating layer solvent can be used as long as it can dissolve the components of the coating layer. There is no specific limitation on its selection. In certain typical but non-limiting embodiments of the present disclosure, the core layer solvent includes at least one of dimethylformamide and N-methylpyrrolidone. The core layer solvent includes dimethylformamide and N-methylpyrrolidone in a mass ratio of (75-135): (60-100). The core layer solvent includes dimethylformamide and N-methylpyrrolidone in a mass ratio of (85-120): (70-90). The coating layer solvent includes at least one of methanesulfonic acid and meta-cresol. The coating layer solvent includes methanesulfonic acid and meta-cresol in a mass ratio of (90-150): (50-100). The coating layer solvent includes methanesulfonic acid and meta-cresol in a mass ratio of (100-130): (60-90).

[0054] The double-layer lithium ion sieve fiber material is a fiber membrane or a fiber line. When the double-layer lithium ion sieve fiber material is a fiber line, its diameter is 0.5 μm to 100 μm, for example, nanometer level (500 to 1000 nm) or micrometer level (1 to 100 μm).

[0055] The present invention provides a method for preparing a double-layer lithium ion sieve fiber material, which comprises: preparing the components of a core layer and a coating layer of the double-layer lithium ion sieve fiber material into a core layer spinning solution and a coating layer spinning solution, placing the core layer spinning solution in a core layer storage tank and the coating layer spinning solution respectively through spinning to form a double-layer fiber intermediate product; subjecting the double-layer fiber intermediate product to acid leaching and pore formation, and then drying to obtain the double-layer lithium ion sieve fiber material.

[0056] Specifically, the steps include:

[0057] S1. Prepare the core layer spinning solution.

[0058] The core layer solvent is mixed with soft polyvinyl chloride and hydrophilic polyethersulfone, heated to 70-85°C, stirred for 5h-7h, cooled to room temperature, and then sodium bicarbonate is added and stirred evenly, and then manganese ion sieve is added and stirred evenly to obtain the core layer spinning solution.

[0059] In the present disclosure, by first mixing soft polyvinyl chloride and hydrophilic polyethersulfone with a core layer solvent, and then adding sodium bicarbonate and manganese ion sieve after the mixture is fully and evenly mixed, the mixture can be evenly dispersed in the solution, and the mixing effect between the components is more uniform.

[0060] S2. Prepare the coating layer spinning solution.

[0061] The coating layer solvent includes methanesulfonic acid and meta-cresol, and the preparation method of the coating layer spinning solution includes: firstly mixing methanesulfonic acid and poly(p-phenylene terephthalamide), heating to 70°C-85°C, stirring for 5h-6h, and obtaining a poly(p-phenylene terephthalamide) solution. Then, meta-cresol is mixed with poly(hexamethylene adipamide), heated to 70°C-85°C, and stirred for 5h-6h to obtain a poly(hexamethylene adipamide) solution. The poly(p-phenylene terephthalamide) solution and the poly(hexamethylene adipamide) solution are mixed, stirred evenly, cooled to room temperature, and then sodium carbonate is added, stirred evenly, and then titanium ion sieve is added, stirred evenly, and the coating layer spinning solution is obtained.

[0062] In the present disclosure, poly(p-phenylene terephthalamide) and poly(hexamethylene adipamide) are prepared into solutions respectively with solvents, which makes it easier to mix the two. Then, sodium carbonate and titanium ion sieve are added to achieve uniform dispersion in the solution, and the mixing effect between the various components is more uniform.

[0063] S3. Spinning.

[0064] The present disclosure utilizes spinning technology to prepare the double-layer material, and the spinning methods include but are not limited to dry spinning, wet spinning or electrospinning.

[0065] The present disclosure provides a typical but non-limiting example, in which coaxial electrospinning is selected for spinning. Specifically, the spinning environment temperature of coaxial electrospinning is 15°C-25°C, the ambient humidity is less than 30%, and the spinning voltage is 15kv-25kv. During coaxial electrospinning, the propulsion flow rate of the core layer spinning solution is 0.18mL / h-0.25mL / h, and the propulsion flow rate of the coating layer spinning solution is 0.28mL / h-0.3mL / h.

[0066] Wherein, the spinning environment temperature can be, for example, any one of 15°C, 18°C, 20°C, 22°C or 25°C, or a range value between any two thereof. The spinning voltage can be, for example, any one of 15kv, 18kv, 20kv, 22kv or 25kv, or a range value between any two thereof. During coaxial electrospinning, the propulsion flow rate of the core layer spinning solution can be, for example, any one of 0.18mL / h, 0.20mL / h, 0.22mL / h, 0.24mL / h or 0.25mL / h, or a range value between any two thereof. The propulsion flow rate of the coating layer spinning solution is any one of 0.28mL / h, 0.29mL / h or 0.3mL / h, or a range value between any two thereof.

[0067] It should be understood that when other spinning methods are selected, the specific process parameters can be adjusted according to actual conditions.

[0068] S4. Acid leaching.

[0069] The double-layer fiber intermediate product is immersed in an acid solution, wherein the acid used for the acid immersion is hydrochloric acid, and the time for the acid immersion is 0.5h-1.5h.

[0070] In the present disclosure, acid solution is used to react with the porogen (sodium carbonate) of the coating layer and the porogen (sodium bicarbonate) of the core layer to generate carbon dioxide. The precipitation of carbon dioxide will form many pores in the material, thereby increasing the porosity of the fiber material.

[0071] S5. Drying.

[0072] The double-layer fiber material after acid leaching is dried to obtain the obtained product. There are many drying methods in the present disclosure, such as ventilation drying, oven drying, etc., as long as the double-layer fiber material can be dried.

[0073] The double-layer lithium ion sieve fiber material prepared by the above method can be widely used as an adsorbent in the extraction of lithium from salt lake brine. The salt lake brine includes at least one of original brine and old brine.

[0074] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0075] Example 1

[0076] The present embodiment provides a double-layer lithium ion sieve fiber material, including a core layer and a coating layer, the core layer includes the following components in parts by weight: 25 parts of manganese ion sieve, 70 parts of soft polyvinyl chloride, 25 parts of hydrophilic polyether sulfone, 75 parts of dimethylformamide, 60 parts of N-methylpyrrolidone, and 15 parts of sodium bicarbonate; the coating layer includes the following components in parts by weight: 25 parts of titanium ion sieve, 45 parts of poly(p-phenylene terephthalamide), 25 parts of poly(hexamethylene adipamide), 90 parts of methanesulfonic acid, 50 parts of m-cresol, and 15 parts of sodium carbonate.

[0077] The preparation method thereof comprises the following steps:

[0078] (1) Preparation of core layer spinning solution: Mix the formulated amounts of dimethylformamide and N-methylpyrrolidone, then add the formulated amounts of soft polyvinyl chloride and hydrophilic polyethersulfone, heat to 80°C, stir for 6 hours, cool to room temperature, then add the formulated amount of sodium bicarbonate, stir evenly, then add the formulated amount of manganese ion sieve, stir evenly, to obtain the core layer spinning solution.

[0079] (2) Preparation of coating layer spinning solution: Take a formulated amount of methanesulfonic acid, add a formulated amount of poly(p-phenylene terephthalamide), heat to 80°C, and stir for 5.5 hours to obtain a poly(p-phenylene terephthalamide) solution; then take a formulated amount of m-cresol, add a formulated amount of poly(hexamethylene adipamide), heat to 80°C, and stir for 5.5 hours to obtain a poly(hexamethylene adipamide) solution; mix the poly(p-phenylene terephthalamide) solution and the poly(hexamethylene adipamide) solution, stir evenly, cool to room temperature, then add a formulated amount of sodium carbonate, stir evenly, and then add a formulated amount of titanium ion sieve, stir evenly, to obtain a coating layer spinning solution.

[0080] (3) Coaxial electrospinning: the core layer spinning solution is placed in a core layer spinning solution storage tank, the coating layer spinning solution is placed in a coating layer spinning solution storage tank, the core layer spinning solution storage tank is connected to the inner tube of the nozzle, the coating layer spinning solution storage tank is connected to the outer tube of the nozzle, the coaxial electrospinning equipment is started, the core layer spinning solution and the coating layer spinning solution are sprayed out from the spray port at the same time, and a double-layer fiber material is formed on the receiving device, and the material is in a film shape; during the coaxial electrospinning process, the ambient temperature is set to 20±5℃, the ambient humidity is less than 30%, the spinning voltage is 20kv, the coating layer melt spinning solution propulsion flow rate is 0.29mL / h, and the core layer spinning solution propulsion flow rate is 0.12mL / h.

[0081] (4) Acid leaching: The obtained double-layer fiber material is immersed in a hydrochloric acid solution for 1 hour.

[0082] (5) Drying: Drying the double-layer fiber material after acid leaching.

[0083] Example 2

[0084] This embodiment is basically the same as embodiment 1, except that the formula of the double-layer lithium ion sieve fiber material is different, as follows:

[0085] A double-layer lithium ion sieve fiber material comprises a core layer and a coating layer, wherein the core layer comprises the following components in parts by weight: 40 parts of manganese ion sieve, 100 parts of soft polyvinyl chloride, 50 parts of hydrophilic polyethersulfone, 135 parts of dimethylformamide, 100 parts of N-methylpyrrolidone, and 30 parts of sodium bicarbonate; and the coating layer comprises the following components in parts by weight: 40 parts of titanium ion sieve, 80 parts of poly(p-phenylene terephthalamide), 50 parts of poly(hexamethylene adipamide), 150 parts of methanesulfonic acid, 100 parts of meta-cresol, and 30 parts of sodium carbonate.

[0086] Example 3

[0087] This embodiment is basically the same as embodiment 1, except that the formula of the double-layer lithium ion sieve fiber material is different, as follows:

[0088] A double-layer lithium ion sieve fiber material comprises a core layer and a coating layer, wherein the core layer comprises the following components in parts by weight: 28 parts of manganese ion sieve, 80 parts of soft polyvinyl chloride, 30 parts of hydrophilic polyether sulfone, 85 parts of dimethylformamide, 70 parts of N-methylpyrrolidone, and 20 parts of sodium bicarbonate; and the coating layer comprises the following components in parts by weight: 28 parts of titanium ion sieve, 50 parts of poly(p-phenylene terephthalamide), 30 parts of poly(hexamethylene adipamide), 100 parts of methanesulfonic acid, 60 parts of meta-cresol, and 18 parts of sodium carbonate.

[0089] Example 4

[0090] This embodiment is basically the same as embodiment 1, except that the formula of the double-layer lithium ion sieve fiber material is different, as follows:

[0091] A double-layer lithium ion sieve fiber material comprises a core layer and a coating layer, wherein the core layer comprises the following components in parts by weight: 38 parts of manganese ion sieve, 90 parts of soft polyvinyl chloride, 45 parts of hydrophilic polyether sulfone, 120 parts of dimethylformamide, 90 parts of N-methylpyrrolidone, and 28 parts of sodium bicarbonate; and the coating layer comprises the following components in parts by weight: 38 parts of titanium ion sieve, 75 parts of poly(p-phenylene terephthalamide), 45 parts of poly(hexamethylene adipamide), 130 parts of methanesulfonic acid, 90 parts of meta-cresol, and 28 parts of sodium carbonate.

[0092] Example 5

[0093] This embodiment is basically the same as embodiment 1, except that the formula of the double-layer lithium ion sieve fiber material is different, as follows:

[0094] A double-layer lithium ion sieve fiber material comprises a core layer and a coating layer, wherein the core layer comprises the following components in parts by weight: 30 parts of manganese ion sieve, 85 parts of soft polyvinyl chloride, 35 parts of hydrophilic polyether sulfone, 110 parts of dimethylformamide, 80 parts of N-methylpyrrolidone, and 27 parts of sodium bicarbonate; and the coating layer comprises the following components in parts by weight: 30 parts of titanium ion sieve, 65 parts of poly(p-phenylene terephthalamide), 35 parts of poly(hexamethylene adipamide), 120 parts of methanesulfonic acid, 80 parts of meta-cresol, and 25 parts of sodium carbonate.

[0095] Example 6

[0096] This embodiment is basically the same as embodiment 1, except that the preparation method is different, as follows:

[0097] (1) Preparation of core layer spinning solution: Mix the formulated amounts of dimethylformamide and N-methylpyrrolidone, then add the formulated amounts of soft polyvinyl chloride and hydrophilic polyethersulfone, raise the temperature to 70°C, stir for 7 hours, cool to room temperature, then add the formulated amount of sodium bicarbonate, stir evenly, then add the formulated amount of manganese ion sieve, stir evenly, to obtain the core layer spinning solution.

[0098] (2) Preparation of coating layer spinning solution: Take a formulated amount of methanesulfonic acid, add a formulated amount of poly(p-phenylene terephthalamide), heat to 70°C, stir for 6 hours, and obtain a poly(p-phenylene terephthalamide) solution; then take a formulated amount of m-cresol, add a formulated amount of poly(hexamethylene adipamide), heat to 70°C, stir for 6 hours, and obtain a poly(hexamethylene adipamide) solution; mix the poly(p-phenylene terephthalamide) solution and the poly(hexamethylene adipamide) solution, stir evenly, cool to room temperature, then add a formulated amount of sodium carbonate, stir evenly, then add a formulated amount of titanium ion sieve, stir evenly, and obtain a coating layer spinning solution.

[0099] (3) Coaxial electrospinning: the core layer spinning solution is placed in a core layer spinning solution storage tank, the coating layer spinning solution is placed in a coating layer spinning solution storage tank, the core layer spinning solution storage tank is connected to the inner tube of the nozzle, the coating layer spinning solution storage tank is connected to the outer tube of the nozzle, the coaxial electrospinning equipment is started, the core layer spinning solution and the coating layer spinning solution are sprayed out from the spray port at the same time, and a double-layer fiber material is formed on the receiving device, and the material is in a film shape; during the coaxial electrospinning process, the ambient temperature is set to 20±5℃, the ambient humidity is less than 30%, the spinning voltage is 15kv, the coating layer melt spinning solution propulsion flow rate is 0.28mL / h, and the core layer spinning solution propulsion flow rate is 0.18mL / h.

[0100] (4) Acid leaching: The obtained double-layer fiber material is immersed in a hydrochloric acid solution for 1 hour.

[0101] (5) Drying: Drying the double-layer fiber material after acid leaching.

[0102] Comparative Example 1

[0103] The difference between Comparative Example 1 and Example 1 is that the core layer spinning solution and the coating layer spinning solution of Example 1 are blended to form a blended solution, and the blended solution is prepared by an electrospinning process, but the electrospinning process is not coaxial electrospinning, but conventional electrospinning. During the electrospinning process, the ambient temperature is set to 20±5°C, the ambient humidity is less than 30%, the spinning voltage is 20kv, and the spinning solution propulsion flow rate is 0.25mL / h.

[0104] The acid leaching and drying process after electrospinning is the same as that in Example 1.

[0105] Comparative Example 2

[0106] The difference between Comparative Example 2 and Example 1 is that the manganese ion sieve of the core layer fiber is replaced by a titanium ion sieve, and the titanium ion sieve of the cladding layer fiber is replaced by a manganese ion sieve.

[0107] Comparative Example 3

[0108] The difference between Comparative Example 3 and Example 1 is that the core layer spinning solution of Example 1 is used as the coating layer spinning solution, and the coating layer spinning solution is used as the core layer spinning solution, but the ion sieve of the core layer spinning solution is still a manganese ion sieve, and the ion sieve of the coating layer spinning solution is still a titanium ion sieve. The details are as follows:

[0109] A double-layer lithium ion sieve fiber material comprises a core layer and a coating layer, wherein the core layer comprises the following components in parts by weight: 25 parts of manganese ion sieve, 45 parts of poly(p-phenylene terephthalamide), 25 parts of poly(hexamethylene adipamide), 90 parts of methanesulfonic acid, 50 parts of meta-cresol, and 15 parts of sodium carbonate; and the coating layer comprises the following components in parts by weight: 25 parts of titanium ion sieve, 70 parts of soft polyvinyl chloride, 25 parts of hydrophilic polyether sulfone, 75 parts of dimethylformamide, 60 parts of N-methylpyrrolidone, and 15 parts of sodium bicarbonate.

[0110] The fiber material obtained in Comparative Example 3 is soft on the outside and hard on the inside, and the coating layer has a stronger hydrophilicity.

[0111] Comparative Example 4

[0112] The difference between Comparative Example 4 and Example 1 is that in the core layer material, the amount of soft polyvinyl chloride is adjusted to 95 parts, and the hydrophilic polyethersulfone is omitted. In the coating layer material, the amount of poly(p-phenylene terephthalamide) is adjusted to 70 parts, and poly(hexamethylene adipamide) is omitted, the amount of methanesulfonic acid is adjusted to 140 parts, and m-cresol is omitted.

[0113] Comparative Example 5

[0114] The difference between Comparative Example 5 and Example 1 is that: in the core layer material, the amount of hydrophilic polyethersulfone is adjusted to 95 parts, and the soft polyvinyl chloride is omitted. In the coating layer material, the amount of polyhexamethylene adipamide is adjusted to 70 parts, polyparaphenylene terephthalamide is omitted, the amount of meta-cresol is adjusted to 140 parts, and methanesulfonic acid is omitted.

[0115] Comparative Example 6

[0116] The difference between Comparative Example 6 and Example 1 is that in the core layer material, the pore-forming agent is adjusted to sodium carbonate, which is the same as the pore-forming agent of the coating layer material.

[0117] Experimental Example 1: Adsorption capacity detection

[0118] Take 100g of the fiber material obtained in Examples 1-6 and Comparative Examples 1-6 respectively to carry out lithium ion adsorption experiments, and place 100g of the fiber material in the experimental brine to extract lithium from the brine. After soaking for 5 hours, soak the fiber material after adsorbing lithium ions with 0.4mol / L hydrochloric acid solution for desorption. After desorption is completed. The fiber material is subjected to the next round of adsorption experiment, and each group of materials repeats 3 rounds of adsorption experiments. The lithium content in the water is determined by inductively coupled plasma atomic emission spectrometry (ICP-OES). The composition of the experimental brine is shown in Table 1 below. The adsorption capacity of the ion sieve fiber material for lithium ions is calculated, and the results are shown in Table 2 below.

[0119] Table 1. Composition of brine used in the experiment

[0120]

[0121] Table 2. Adsorption capacity result record

[0122]

[0123]

[0124] From the records in Table 2, it can be seen that the double-layer lithium ion sieve fiber materials of Examples 1-6 have a large adsorption capacity for lithium ions and good cycle performance, which shows that during the adsorption and desorption process, the dissolution loss of the ion sieve in the material is small.

[0125] The fiber material obtained in Comparative Example 1 is not a double-layer material, the manganese ion sieve is not protected by the coating layer fiber, and the hydrophilic fiber material is not placed in the core layer, which will lead to a large dissolution loss of the manganese ion sieve, thereby causing a decrease in adsorption cycle performance. In addition, the high molecular polymer used in the formula is blended with the two ion sieves, which may also affect the uniform distribution of the ion sieve, or block the adsorption sites of the ion sieve, resulting in a decrease in adsorption energy.

[0126] In comparative example 2, the manganese ion sieve is placed in the fiber material coating layer, and the titanium ion sieve is placed in the fiber material core layer. The manganese ion sieve in the coating layer has a large dissolution loss, resulting in poor adsorption cycle performance.

[0127] In Comparative Example 3, the core layer spinning solution of Example 1 is used as the coating layer spinning solution, and the coating layer spinning solution is used as the core layer spinning solution. The fiber material coating layer obtained in Comparative Example 3 is more hydrophilic, which will increase the dissolution loss of the ion sieve and cause a decrease in the adsorption cycle performance.

[0128] In Comparative Example 4, hydrophilic polyethersulfone is omitted in the core layer material, and polyhexamethylene adipamide and m-cresol are omitted in the coating layer material. At this time, the lack of modification of the core layer by hydrophilic polyethersulfone will significantly reduce the hydrophilicity, permeability and wettability of the fiber material. At the same time, since both polyhexamethylene adipamide and poly(p-phenylene terephthalamide) can provide strength for the skeleton material, the two are used in combination for better effect. Omitting polyhexamethylene adipamide will lead to a decrease in the strength of the skeleton material. When the hydrophilicity and strength are affected, the distribution of lithium ions in the material will also be affected, resulting in a decrease in adsorption amount and a decrease in cycle performance.

[0129] The hydrophilicity of Comparative Example 5 is stronger, which is conducive to the wetting of the fiber membrane in water, thereby improving the adsorption. However, due to the increased water solubility, the adsorption cycle stability is poor.

[0130] In the fiber material of Comparative Example 6, the pore-forming agent of the fiber materials of the core layer and the coating layer is sodium carbonate. The speed and ability of the core layer fiber to generate bubbles during pore formation are weaker than those in Example 1, which will affect the pore formation of the fiber material, resulting in a decrease in the adsorption amount and adsorption cycle performance.

[0131] Experimental Example 2: Elongation at Break Test

[0132] At room temperature, the fiber materials obtained from Examples 1-6 and Comparative Examples 1-6 were tested for elongation at break using an elongation tester FL-8610A. The elongation at break test method was performed according to the instrument's instruction manual. The results are shown in Table 3 below.

[0133] Table 3. Elongation at break test result record

[0134] Elongation at break Example 1 135% Example 2 133% Example 3 129% Example 4 131% Example 5 131% Example 6 125% Comparative Example 1 102% Comparative Example 2 122% Comparative Example 3 108% Comparative Example 4 99% Comparative Example 5 114% Comparative Example 6 126%

[0135] It can be seen from Table 3 that the double-layer lithium ion sieve fiber materials obtained in Examples 1-6 have relatively large elongations at break, which indicates that the fiber materials are relatively strong and not prone to breakage, and are suitable for long-term use in brine. The fiber material of Comparative Example 1 is not a double-layer material, but a single-layer fiber formed by blending all materials. Its elongation at break is lower than that of the embodiment, and it is more prone to breakage. In Comparative Example 3, the core layer spinning solution of Example 1 is used as the coating layer spinning solution, and the coating layer spinning solution is used as the core layer spinning solution. The fiber obtained is soft on the outside and hard on the inside, and its mechanical properties are weaker than those of Example 1, and it is easier to break. The composition of the core layer and the coating layer of the fiber materials of Comparative Examples 4 and 5 were adjusted, resulting in a decrease in elongation at break. The formation of pores in Comparative Example 6 is poor, resulting in its elongation at break being slightly lower than that of Example 1.

[0136] In summary, the double-layer lithium ion sieve fiber material provided by the present invention optimizes the formula of the core layer material and the coating layer material, and obtains a fiber material that is rigid on the outside and soft on the inside. The coating layer fiber has good rigidity, high strength, and is not easy to break, and plays a good supporting role. It can resist water pressure well and better maintain the structural integrity of the fiber material; the core layer fiber has good flexibility, which can further reduce the probability of material breakage during use. The core layer material does not directly contact brine during use, and the present invention modifies the core layer material by using hydrophilic polyethersulfone, which improves the inward penetration and infiltration of brine, thereby improving the adsorption performance of lithium ions.

[0137] The double-layer lithium ion sieve fiber material provided by the present invention places the manganese ion sieve, which is more easily dissolved, in the core layer of the fiber material, and the coating layer fiber material forms a protective layer for the manganese ion sieve, thereby reducing the direct contact between the acid and the manganese ion sieve, inhibiting the corrosion of the acid to the manganese ion sieve, thereby reducing the dissolution of the manganese ion sieve and ensuring the circulation performance of the fiber material.

[0138] The double-layer lithium ion sieve fiber material provided by the present invention adopts sodium carbonate as the pore-forming agent for the coating layer fibers and sodium bicarbonate as the pore-forming agent for the core layer fibers, so that the fibers can form more pores. At the same time, the bubbles generated when the core layer fibers are pore-formed are discharged from the inside to the outside, further promoting the formation of pores.

[0139] The preparation method of the double-layer lithium ion sieve fiber material provided in the present invention adopts the spinning process technology. The fiber material obtained by spinning has high porosity and large specific surface area. Then, pores are formed by an acid leaching pore-forming process. During the acid leaching process, the precipitation of carbon dioxide further increases the porosity of the fiber material, so that the lithium ion sieve exposes more adsorption sites, thereby increasing the adsorption amount of lithium ions.

[0140] The preparation method of the double-layer lithium ion sieve fiber material provided by the present disclosure can obtain a fiber material that can be a fiber membrane or a fiber line. The specific form can be set according to actual needs. The membrane fiber can be directly used for lithium extraction; the linear fiber can be first filled into a column and then used for lithium extraction. Alternatively, the linear fiber can be spun to form a fiber yarn with a larger diameter, and the fiber yarn is integrated into a fiber bundle, and lithium is directly extracted in brine through the fiber bundle.

[0141] The optional implementation modes of the present disclosure are described in detail above, but the present disclosure is not limited thereto. Within the technical concept of the present disclosure, the technical solution of the present disclosure can be subjected to a variety of simple modifications, including combining various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present disclosure and belong to the protection scope of the present disclosure.

[0142] Industrial Applicability

[0143] The double-layer lithium ion sieve fiber material provided by the present disclosure optimizes the formula of the core layer material and the coating layer material, and obtains a fiber material that is rigid on the outside and soft on the inside. The coating layer fiber has good rigidity, high strength, and is not easy to break, which plays a good supporting role, can well resist water pressure, and better maintain the structural integrity of the fiber material; the core layer fiber has good flexibility, which can further reduce the probability of material breakage during use. The core layer material does not directly contact the brine during use, and the present disclosure improves the inward penetration and infiltration of brine by using hydrophilic polyethersulfone to modify the core layer material, thereby improving the adsorption performance of lithium ions. The double-layer lithium ion sieve fiber material provided by the present disclosure places the manganese ion sieve that is more easily dissolved in the core layer of the fiber material, and the coating layer fiber material forms a protective layer for the manganese ion sieve, reducing the direct contact between the acid and the manganese ion sieve, inhibiting the corrosion of the acid to the manganese ion sieve, thereby reducing the dissolution of the manganese ion sieve and ensuring the circulation performance of the fiber material. The preparation method of the double-layer lithium ion sieve fiber material provided in the present invention is prepared by a spinning process technology. The fiber material obtained by spinning has a high porosity and a large specific surface area. Then, pores are formed by an acid leaching pore-forming process. Since the present invention adopts sodium carbonate as a coating layer fiber pore-forming agent and sodium bicarbonate as a core layer fiber pore-forming agent, the fiber can form more pores. At the same time, the bubbles generated when the core layer fiber is pore-formed are discharged from the inside to the outside, further promoting the formation of pores. During the acid leaching process, the precipitation of carbon dioxide further increases the porosity of the fiber material, so that the lithium ion sieve exposes more adsorption sites and increases the adsorption amount of lithium ions. The prepared double-layer lithium ion sieve fiber material can be widely used in brine for lithium extraction.

Claims

1. A double-layer lithium ion sieve fiber material, characterized in that: It includes a core layer and a cladding layer from the inside to the outside; The core layer includes a flexible carrier and a manganese ion sieve dispersed in the flexible carrier, the flexible carrier is composed of soft polyvinyl chloride and hydrophilic polyethersulfone, and a plurality of first holes are constructed on the flexible carrier; The coating layer includes a rigid carrier and a titanium ion sieve dispersed in the rigid carrier, the rigid carrier is composed of poly(p-phenylene terephthalamide) and poly(hexamethylene adipamide), and a plurality of second holes are constructed on the flexible carrier; The double-layer lithium ion sieve fiber material is a fiber membrane or a fiber wire.

2. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The thickness ratio of the core layer to the cladding layer is 1:(1-3).

3. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The specific surface area of ​​the core layer is 5m 2 / g-12m 2 / g.

4. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The specific surface area of ​​the coating layer is 5m 2 / g-12m 2 / g.

5. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The mass ratio of the manganese ion sieve, the soft polyvinyl chloride and the hydrophilic polyether sulfone is (25-40): (70-100): (25-50).

6. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The mass ratio of the titanium ion sieve, the poly(p-phenylene terephthalamide) and the poly(hexamethylene adipamide) is (25-40): (45-80): (25-50).

7. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The density of the soft polyvinyl chloride is 1.2 g / cm 3 -1.3g / cm 3 , the yield strength is 15MPa-25MPa.

8. The double-layer lithium ion sieve fiber material according to claim 1, characterized in that: The diameter of the fiber line is 0.5 μm-100 μm.

9. A method for preparing a double-layer lithium ion sieve fiber material, characterized in that: It includes: The manganese ion sieve, soft polyvinyl chloride, hydrophilic polyethersulfone, core layer solvent and sodium bicarbonate are mixed to form a core layer spinning solution; The titanium ion sieve, poly(p-phenylene terephthalamide), poly(hexamethylene adipamide), a coating layer solvent and sodium carbonate are mixed to form a coating layer spinning solution; Spinning the core layer spinning solution and the cladding layer spinning solution to form a double-layer fiber intermediate product in which the cladding layer covers the core layer; The double-layer fiber intermediate product is subjected to acid leaching to form pores, and then dried to obtain the double-layer lithium ion sieve fiber material.

10. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The mass ratio of the manganese ion sieve, the soft polyvinyl chloride, the hydrophilic polyethersulfone, the core layer solvent and the sodium bicarbonate is (25-40): (70-100): (25-50): (135-235): (15-30).

11. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The core layer solvent includes at least one of dimethylformamide and N-methylpyrrolidone.

12. The method for preparing a double-layer lithium ion sieve fiber material according to claim 11, characterized in that: The core layer solvent comprises dimethylformamide and N-methylpyrrolidone in a mass ratio of (75-135):(60-100).

13. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The mass ratio of the titanium ion sieve, the poly(p-phenylene terephthalamide), the poly(hexamethylene adipamide), the coating layer solvent and the sodium carbonate is (25-40): (45-80): (25-50): (140-250): (15-30).

14. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The coating layer solvent includes at least one of methanesulfonic acid and m-cresol.

15. The method for preparing a double-layer lithium ion sieve fiber material according to claim 14, characterized in that: The coating layer solvent comprises methanesulfonic acid and meta-cresol in a mass ratio of (90-150):(50-100).

16. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The spinning includes dry spinning, wet spinning or electrostatic spinning.

17. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The spinning is coaxial electrostatic spinning.

18. The method for preparing a double-layer lithium ion sieve fiber material according to claim 17, characterized in that: The spinning environment temperature of the coaxial electrostatic spinning is 15° C.-25° C., the environmental humidity is less than 30%, and the spinning voltage is 15 kv-25 kv.

19. The method for preparing a double-layer lithium ion sieve fiber material according to claim 17, characterized in that: During the coaxial electrospinning, the propulsion flow rate of the core layer spinning solution is 0.18-0.25 mL / h, and the propulsion flow rate of the coating layer spinning solution is 0.10 mL / h-0.15 mL / h.

20. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The acid used for pickling is hydrochloric acid.

21. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The acid leaching time is 0.5h-1.5h.

22. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The preparation method of the core layer spinning solution comprises: mixing the core layer solvent with the soft polyvinyl chloride and the hydrophilic polyethersulfone, heating to 70°C-85°C, stirring for 5h-7h, cooling to room temperature, then adding the sodium bicarbonate, stirring evenly, and then adding the manganese ion sieve, stirring evenly to obtain the core layer spinning solution.

23. The method for preparing a double-layer lithium ion sieve fiber material according to claim 9, characterized in that: The coating layer solvent includes methanesulfonic acid and isocresol. The preparation method of the coating layer spinning solution includes: firstly mixing the methanesulfonic acid and the poly(p-phenylene terephthalamide), heating to 70°C-85°C, stirring for 5h-6h, and obtaining a poly(p-phenylene terephthalamide) solution; then mixing the isocresol with the poly(hexamethylene adipamide), heating to 70°C-85°C, stirring for 5h-6h, and obtaining a poly(hexamethylene adipamide) solution; mixing the poly(p-phenylene terephthalamide) solution and the poly(hexamethylene adipamide) solution, stirring evenly, cooling to room temperature, then adding the sodium carbonate, stirring evenly, and then adding the titanium ion sieve, stirring evenly, and obtaining the coating layer spinning solution.

24. Use of the double-layer lithium ion sieve fiber material as claimed in claim 1 or the double-layer lithium ion sieve fiber material prepared by the preparation method of the double-layer lithium ion sieve fiber material as claimed in claim 9 as an adsorbent in lithium extraction from salt lake brine.

25. The use according to claim 24, characterized in that The salt lake brine includes at least one of original brine and old brine.

Citation Information

Patent Citations

  • Preparation method of porous spinning composite material and lithium extraction application thereof

    CN112619621A

  • Lithium ion adsorption material, preparation method thereof, lithium extraction system and lithium extraction method

    CN115970659A